2010
DOI: 10.1063/1.3409691
|View full text |Cite
|
Sign up to set email alerts
|

Use of a GaAsSb buffer layer for the formation of small, uniform, and dense InAs quantum dots

Abstract: InAs quantum dots grown on GaAsSb buffer layers with varying Sb content have been studied. Atomic force microscopy results show that the dot size is reduced as the Sb content increases with a concomitant increase in number density. Analysis of the size distribution indicates that the spread of dot sizes narrows with increasing Sb content. This is confirmed by photoluminescence measurements showing a significant narrowing of the dot emission peak for a GaAs0.77Sb0.23 buffer compared to a GaAs buffer. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…When the CL covers a QD, nitrogen fosters the Sb to accumulate on top of the partially relaxed InAs QDs since GaSb has a very similar lattice constant with InAs. On the other hand, as the composition threshold for the total restraint of GaAsSb/InAs QD dissolution in the capping process is around 11% to 14% of Sb [26,27], we could assume that the dissolution process of InAs QDs during the capping growth is completely suppressed for both samples and that the In atoms are not being relocated from the top of the QDs to the QD base [1,7,28]. This explains why no significant differences in the size and morphology of the QDs are seen in both samples.…”
Section: Resultsmentioning
confidence: 99%
“…When the CL covers a QD, nitrogen fosters the Sb to accumulate on top of the partially relaxed InAs QDs since GaSb has a very similar lattice constant with InAs. On the other hand, as the composition threshold for the total restraint of GaAsSb/InAs QD dissolution in the capping process is around 11% to 14% of Sb [26,27], we could assume that the dissolution process of InAs QDs during the capping growth is completely suppressed for both samples and that the In atoms are not being relocated from the top of the QDs to the QD base [1,7,28]. This explains why no significant differences in the size and morphology of the QDs are seen in both samples.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray and TEM data shown that density of dislocation loops increased from 2 -3 10 2 cm -1 , almost the same for both {110} directions at 8% Sb structure to significantly anisotropic in 16% Sb structure, from 1 10 4 cm -1 for [110] direction up to 4 10 4 cm -1 for [1][2][3][4][5][6][7][8][9][10] direction. RSM (224) reflection picture measured for [1][2][3][4][5][6][7][8][9][10] azimuth direction revealed small anisotropic relaxation of initial elastic stress ( 6.5 ± 1.5%) in this structure. X-ray investigations of 37% Sb composition structure demonstrated significant increase of structural deterioration: total density of 60 secondary dislocation loops in the volume of this structure increased up to 1.25 10 10 cm -2 while vertical and lateral coherence lengths diminished by few times.…”
Section: X-ray and Tem Datamentioning
confidence: 86%
“…To effectively realize these devices, particularly the IBSCs, control of the QD structural and optoelectronic properties is required. The tunability of self-assembled QDs depends on the impact of growth parameters such as substrate temperature, deposition rate and stoichiometry on atom's deposition [5,6]. For most QDs devices high density of QDs with near identical morphology is desired.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] In order to realize IBSCs with the InAs QDs, it is required to simultaneously achieve high density and uniformity of QDs for the high light absorption. [3] According to our previous work InAs/GaAsSb is one of the most promising material systems since it has small valence band offset (VBO) and gives good QD properties such as small size, high density and uniformity by Sb content. [3,4] At this point, it is crucial to investigate optical properties of InAs/GaAsSb to address its band structure.…”
Section: Introductionmentioning
confidence: 99%